Prediksi Pengunduran Diri Karyawan Dengan Pendekatan Deep Neural Network Dalam Machine Learning - Wirapati, Satya; Astuti, Luh Gede; Widiartha, I Made; Santiyasa, I Wayan (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2024)
In the current digital era, technological advancements are rapidly progressing and impacting various sectors, including the workforce. Employees are crucial assets for companies to achieve their business goals. Therefore, companies need to take steps to retain quality and potential employees, as well as avoid unwanted employee turnover. Employee turnover can incur significant costs for companies, such as recruitment expenses, training costs, and loss of productivity. Hence, companies need to have the ability to predict which employees are likely to resign, so they can take appropriate actions to retain them. In this regard, machine learning techniques can be an effective solution for predicting employee turnover. By using the right machine learning algorithms, companies can identify the factors influencing employees' decisions to resign and take appropriate actions to retain them. Therefore, this research aims to apply machine learning techniques in predicting employee turnover. It is hoped that the results of this research can help companies identify the factors influencing employee turnover and take appropriate actions to retain them, thereby improving overall company performance.